Stable isotope analysis to assess the trophic level of arthropod in sugarcane ratoon agroecosystem - HERI PRABOWO; BAMBANG TRI RAHARDJO; GATOT MUDJIONO; AKHMAD RIZALI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Prabowo H, Rahardjo BT, Mudjiono G, Rizali A. 2022. Stable isotope analysis to assess the trophic level of arthropod in sugarcane ratoon agroecosystem. Biodiversitas 23: 2871-2881. Arthropods represent one of the main components of soil inhabitants and play an important role in maintaining soil health, as well as providing ecosystem services. The description of the trophic level of the ratoon sugarcane agroecosystem is needed to describe the role of organisms in the ecosystem to maximize the role of detritivores, predators, and parasitoids in the ratoon sugarcane agroecosystem. The stable isotope approach is widely used in various studies to describe trophic levels in an agroecosystem. The stable isotope technique, especially the one that uses stable isotopes of carbon (?13C) and nitrogen (?15N), can measure the trophic position that integrates energy assimilation or mass flow through all the different trophic pathways leading to an organism. Stable isotopes ?13C and ?15N can be used to identify the roles of arthropods in the ratoon sugarcane agroecosystem by identifying the composition of both isotopes. The ratio of arthropod's carbon assimilation (?13C) to sugarcane ranges from-1.4 to-5.45‰. In contrast, the ratio of nitrogen assimilation (?15N) of arthropod to sugarcane ranges from 3.86 to 39.7‰. The values of stable isotope ?13C and ?15N on predator and parasitoids are varied. The stable isotope value of carbon (?13C) for predators varies from-10.14 to-11.62‰. In contrast, the predator's stable isotope value of nitrogen (?15N) varies from 9.17 to 18.1%. The parasitoids' carbon stable isotope value (?13C) varies from 10.5 to 11.05‰. In contrast, parasitoids' nitrogen stable isotope value (?15N) varies from 12.8 to 17.05‰. The value of carbon (?13C) stable isotope assimilation between herbivores and predators varies from 0.006 to 1.38‰. While the value of nitrogen (?15N) stable isotope assimilation varies in the range of 0.33 to 10.3‰. Furthermore, the value of carbon (?13C) stable isotope assimilation between herbivores and parasitoids varies in the range of 5.3 to 9.23‰. While the value of nitrogen (?15N) stable isotope assimilation varies in the range of 3.79 to 10.3‰. Isotope content (?13C) shows the food resources of arthropods in the agroecosystem, while isotope value (?15N) shows the roles of arthropods in the sugarcane ratoon agroecosystem. Carbon stable isotope values of predator and parasitoids are close to zero. While the stable nitrogen isotope (?15N) values on arthropods are averagely above 10‰, values are suspected of having roles as predators or parasitoids. Knowing the trophic level of predators and parasitoids through stable isotopes in agroecosystems can be used to conserve and optimize natural enemies to suppress the development of herbivores.